2009
DOI: 10.1089/clo.2009.0005
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation Development of Somatic Cell Cloned Embryos in the Common Marmoset (Callithrix jacchus)

Abstract: The somatic cell nuclear transfer technique has been applied to various mammals to produce cloned animals; however, a standardized method is not applicable to all species. We aimed here to develop optimum procedures for somatic cell cloning in nonhuman primates, using common marmosets. First, we confirmed that parthenogenetic activation of in vitro matured oocytes was successfully induced by electrical stimulation (three cycles of 150 V/mm, 50 microsec x 2, 20 min intervals), and this condition was applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…Such stimuli also enhanced the development of ICSI-derived embryos in these species (Probst & Rath, 2003;Suttner et al, 2000). For marmosets, information on artificial oocyte activation is limited, although it was reported that diploid parthenogenetic embryos produced by electric stimulation developed to the 8-cell stage (Sotomaru et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such stimuli also enhanced the development of ICSI-derived embryos in these species (Probst & Rath, 2003;Suttner et al, 2000). For marmosets, information on artificial oocyte activation is limited, although it was reported that diploid parthenogenetic embryos produced by electric stimulation developed to the 8-cell stage (Sotomaru et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The common marmoset (Callithrix jacchus) has been used extensively for biomedical research because of its advantages of small size, ease of handling, and a relatively short gestation period (143-148 days). In 2009, it was reported that transgenic marmosets expressing enhanced green fluorescent protein were born and the transgene could be transmitted to offspring by in vitro fertilization (Sasaki et al, 2009). This was the first report on the establishment of gene-modified lines of primates.…”
mentioning
confidence: 99%
“…This, coupled with the development of somatic cell cloned embryos [17], the ability to produce induced pluripotent stem cells [18], and the aforementioned husbandry benefits, has ensconced the marmoset as a major new player in non-human primate research going forward. Several years prior, Callithrix jacchus was selected as the first New World monkey genome to be sequenced.…”
Section: Introductionmentioning
confidence: 99%
“…Controlled ovarian stimulation in non-human primates is routinely induced by administration of exogenous gonadotropins (Sotomaru et al , 2009; Zelinski-Wooten et al , 1995). In rhesus macaques, starting at menses (day 1–4 of their menstrual cycle), females receive twice-daily injections of recombinant human follicle stimulating hormone (FSH; Organon; 30 IU, im) for 8 days and recombinant human luteinizing hormone (LH; Ares Serono; 30 IU, im) on days 7–8 of the stimulation protocol.…”
Section: Oocyte Productionmentioning
confidence: 99%
“…In our current protocols, we recover oocytes 35–36 hours post-hCG to allow oocyte maturation and spindle migration away from the polar body, thus making it easier to visualize and enucleate the meiotic spindle. In the common marmoset, ovarian stimulation commonly entails a single, daily injection of 50 IU FSH for 11 days, followed by the administration of 75 IU hCG on the 12 th day of the stimulation protocol (Sotomaru et al , 2009). Germinal vesicle-stage oocytes, enclosed in cumulus cell-oocyte complexes, are recovered 16 hours post-hCG injection and placed in maturation medium for approximately 22–24 hours (Sotomaru et al , 2009).…”
Section: Oocyte Productionmentioning
confidence: 99%